The tower of Nero - Riordan, Rick (Riordan, Rick. Trials of Apollo, 2020)
Will the Greek god Apollo, cast down to Earth in the pathetic mortal form of a teenager named Lester Papadopoulos, finally regain his place on Mount Olympus? Lester's demigod friends at Camp Jupiter just helped him survive attacks from bloodthirsty ghouls, an evil Roman king and his army of the undead, and the lethal emperors Caligula and Commodus. Now the former god and his demigod master Meg must follow a prophecy uncovered by Ella the harpy. Lester's final challenge will be at the Tower of Nero, back in New York. Will Meg have a last showdown with her father? Will this helpless form of Apollo have to face his arch-nemesis, Python? Who will be on hand at Camp Half-Blood to assist? These questions and more will be answered in this book that all demigods are eagerly awaiting.